2015
DOI: 10.1016/j.enpol.2014.10.024
|View full text |Cite
|
Sign up to set email alerts
|

Modelling the energy and exergy utilisation of the Mexican non-domestic sector: A study by climatic regions

Abstract: This paper presents the development of a bottom-up stock model to perform a holistic energy study of the Mexican non-domestic sector. The current energy and exergy flows are shown based on a categorisation by climatic regions with the aim of understanding the impact of local characteristics on regional efficiencies. Due to the limited data currently available, the study is supported by the development of a detailed archetype-based stock model using EnergyPlus as a first law analysis tool combined with an exist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 26 publications
(35 reference statements)
1
2
0
1
Order By: Relevance
“…A similar comparison can already be found in García Kerdan, Morillón Gálvez et al (2015). Table 6 shows a comaprison among regions.…”
Section: Comparison With Other Studiessupporting
confidence: 65%
“…A similar comparison can already be found in García Kerdan, Morillón Gálvez et al (2015). Table 6 shows a comaprison among regions.…”
Section: Comparison With Other Studiessupporting
confidence: 65%
“…Através dela, é possível identificar que dos 21 artigos selecionados, 13 (SOARES GERALDI et al, 2022;PERWEZ et al, 2022;YAMAGUCHI et al, 2022;CARNIELETTO et al, 2021;BIANCHI et al , 2020;ZHENGYU;YIHUA, 2020;KIM et al, 2019;ELHARIDI;TUOHY;TEAMAH, 2018;ELHARIDI, 2017;KIMURA et al, 2017;GARCÍA KERDAN et al, 2015; MATA; SASIC KALAGASIDIS; JOHNSSON, 2014; KOROLIJA, 2013) levaram em consideração as características físicas da edificação no processo de elaboração de arquétipos, o que demonstra a importância da obtenção destes dados, uma vez que informações como o percentual de abertura da fachada (PAF) e formato da edificação apresentam influência direta nos resultados de desempenho termoenergético. Outros cinco estudos (TAM NGUYEN et al, 2019;YAMAGUCHI et al, 2022;SOARES GERALDI et al, 2022;GARCÍA KERDAN et al, 2015; MATA; SASIC KALAGASIDIS; JOHNSSON, 2014) fizeram uso de bases de dados, como dados governamentais, censo estatístico, dados meteorológicos, registro de empresas e organizações públicas; e dois (ALVES, 2017, 2018) utilizaram a legislação vigente no local do estudo, como por exemplo leis de uso do solo e código de obras. Oito trabalhos (SOARES GERALDI et al, 2022;ZHENGYU;YIHUA, 2020;KIM et al, Dentre os artigos selecionados, três foram realizados no Brasil (SOARES GERALDI et al, 2022;ALVES, 2017ALVES, , 2018.…”
Section: Arquétipos De Edifícios Comerciaisunclassified
“…As such, we recreate the occupancy for March 15, 1986, based on reports of missing hotel staff, bank staff (Crossette, 1986), and night club staff and occupancy (National Geographic, 2005), as well as original estimates of 300 people feared missing (New York Times, 1986). These points of verification are used in combination with typical building occupancy by hour, separated by building type (García Kerdan et al, 2015). Results from this occupancy estimation and relaxation of historical parameters (Step 4) are presented in Figure 2.…”
Section: A Downward Counterfactual Shift In Timementioning
confidence: 99%
“…In Singapore, severe haze episodes arise from the compound conditions of wildfires and/or human-caused fires, dry conditions (exacerbated by the periodic warming of sea surface temperatures of El Niño years, which can cause drought, food insecurity, and more), and prevailing wind patterns (Forsyth, 2014). Haze is also a transboundary issue FIGURE 2 | Hotel New World estimated occupancy by hour for the day of collapse based on typical occupancy for building use and type (García Kerdan et al, 2015), as well as original estimates and accounts of persons reported missing (New York Times, 1986;National Geographic, 2005).…”
Section: Haze In Southeast Asiamentioning
confidence: 99%